The consumer protection laws: an overview / Khairul Anuar Abdul Rahman - Abdul Rahman, Khairul Anuar (Faculty of Architecture, Planning & Surveying, 1987)
The objective of this study is to examine the consumer protection laws generally. There are many questions in relation to the law in particular, inter alia: Who are protected by the law? What are the rights of the class person protected under the law? To what extent are they protected? This study is to give the consumer a general idea of law relating to consumer protection. It provides such as guide for the layman to protect his interest as a consumer in a simple terms. Basic consumer legislations on consumer protection to them are fulfilled through this study.